2016
DOI: 10.1007/s00592-016-0867-8
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma fatty acid-binding protein 4 (FABP4) as a novel biomarker to predict gestational diabetes mellitus

Abstract: These results suggest that serum FABP4 may potentially serve as a novel biomarker for the prediction of GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 61 publications
9
29
0
Order By: Relevance
“…FABP4 promoter has a binding site for insulin, fatty acids, and hypoxia-inducible factor [60,61], and these are all increased in GDM conditions [45,62,63], possibly contributing to FABP3 and FABP4 promoter activation and upregulation. Consistent with our findings, increased placental FABP3 and FABP4 expression and a strong correlation of circulatory FABP4 levels with GDM have been reported [27,64].…”
Section: Discussionsupporting
confidence: 93%
“…FABP4 promoter has a binding site for insulin, fatty acids, and hypoxia-inducible factor [60,61], and these are all increased in GDM conditions [45,62,63], possibly contributing to FABP3 and FABP4 promoter activation and upregulation. Consistent with our findings, increased placental FABP3 and FABP4 expression and a strong correlation of circulatory FABP4 levels with GDM have been reported [27,64].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, FABP4 and OC levels were elevated in both second and third trimester, which indicated that occasion of measurement may not influence the relationship of FABP4 and OC concentrations with GDM. Consequently, it was assumed that GDM was described as a rise of FABP4 and OC, in line with findings supported by Ning et al [52] and Abell et al [53]. Moreover, the measurement method possibly was a source of heterogeneity across the seven studies, but subgroup analysis stratified by the measurement method showed a discrepant result when the OC levels were detected by IRMA.…”
Section: Discussionsupporting
confidence: 61%
“…FABP4, also known as adipocyte FABP (A-FABP), is a member of a lipid-binding protein super-family. FABP4 is highly expressed in adipocytes and consists of about 1% of all soluble proteins in the adipose tissue [19]. Expression of FABP4 is highly induced during adipocyte differentiation and transcriptionally controlled by peroxisome proliferator-activated receptor γ (PPARγ) agonists, unsaturated long-chain fatty acids, dexamethasone, and insulin-like growth factor 1 [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…FABP4 is highly expressed in adipocytes and consists of about 1% of all soluble proteins in the adipose tissue [19]. Expression of FABP4 is highly induced during adipocyte differentiation and transcriptionally controlled by peroxisome proliferator-activated receptor γ (PPARγ) agonists, unsaturated long-chain fatty acids, dexamethasone, and insulin-like growth factor 1 [19,20,21]. FABP4 is also detected in a subset of the endothelial cells and macrophages, where it increases accumulation of cholesterol ester and foam cell formation via inhibition of the PPARγ-liver X receptor α (LXRα)-ATP-binding cassette A1 (ABCA1) pathway and induces inflammatory responses through activation of the IKK-NF-κB and JNK-AP-1 pathways [21].…”
Section: Introductionmentioning
confidence: 99%